Effects of Yeast-lactic Acid Bacteria Co-fermentation on the Quality of Navel Orange Beverage - Hong YE; Xuerui ZHOU; Su WANG; Yingyue ZHANG; Yue SUN; Chaoyi ZENG; Qing ZHANG; Jie TANG (Shipin gongye ke-ji, 2023)
To study the fermentation characteristics of Saccharomyces cerevisiae (SC-125) and Lactobacillus plantarum (B-5) in mixed bacterial fermentation, fresh Jintang navel orange juice was used as raw material and inoculated with the two bacteria separately for co-fermentation, to investigate the changes in the number of viable bacteria, pH, reducing sugar, alcohol, and The changes of basic physicochemical indexes such as viable bacteria, pH, reducing sugar, alcoholic content and total phenols were investigated, and the scavenging ability of DPPH and hydroxyl radicals of navel orange drinks were examined. The results showed that the yeast in the co-fermented navel orange beverage increased rapidly to 8.0 CFU·mL−1 and the reduced sugar content decreased rapidly during 0~36 h of fermentation compared with the navel orange drink prepared by single-strain fermentation. The final alcohol content of co-fermentation was 5.33%, which was lower than that of brewer's yeast SC-125 alone. The total phenolic content, DPPH radicals and hydroxyl radical scavenging capacity of co-fermentation increased, reaching 355.5 mg·L−1, 78.82%, and 77.08%, respectively. Co-fermentation volatile components were more abundant, with 51 aroma substances detected, including 9 unique aroma substances, namely: Isopropyl format, ethyl undecanoate, isobutyl acetate, methyl butyrate, tetrahydro linalool, 1-tetradecanol, 2-pentanol, undecylenic aldehyde, 2-nitropropane, giving navel orange drinks nutty, coconut and rose aromas. The principal component analysis of the electronic nose showed that the co-fermentation was more sensitive to three sensors, W5S, W1S and W2S, mainly nitrogen oxides, short chain alkanes and ethanol. This study would provide a theoretical basis for the development of navel orange beverages.